2020
DOI: 10.1177/0272989x20940673
|View full text |Cite
|
Sign up to set email alerts
|

Implausible States: Prevalence of EQ-5D-5L States in the General Population and Its Effect on Health State Valuation

Abstract: The EQ-5D is made up of health state dimensions and levels, in which some combinations seem less “plausible” than others. If “implausible” states are used in health state valuation exercises, then respondents may have difficulty imagining them, causing measurement error. There is currently no standard solution: some valuation studies exclude such states, whereas others leave them in. This study aims to address 2 gaps in the literature: 1) to propose an evidence-based set of the least prevalent two-way combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Quality of life was impaired in the FND sample (Table 2); patients' mean EQ‐5D‐5L health state valuation score (0.55) was markedly less than (EQ‐5D‐3L) norms observed in age‐matched healthy UK populations (which across 10‐year age cohorts from 25–75 years range from 0.93–0.78 [23]). Problems concerning pain/discomfort (75.6%), mood disturbances (80.3%) and carrying out usual activities (83.4%) were domains most affected, with considerably higher rates than self‐reported EQ‐5D‐5L problems observed in a large sample of the general population in England (53.6%, 31.4% and 30.2%, respectively [24].…”
Section: Resultsmentioning
confidence: 99%
“…Quality of life was impaired in the FND sample (Table 2); patients' mean EQ‐5D‐5L health state valuation score (0.55) was markedly less than (EQ‐5D‐3L) norms observed in age‐matched healthy UK populations (which across 10‐year age cohorts from 25–75 years range from 0.93–0.78 [23]). Problems concerning pain/discomfort (75.6%), mood disturbances (80.3%) and carrying out usual activities (83.4%) were domains most affected, with considerably higher rates than self‐reported EQ‐5D‐5L problems observed in a large sample of the general population in England (53.6%, 31.4% and 30.2%, respectively [24].…”
Section: Resultsmentioning
confidence: 99%
“…This is because it is difficult to make a judgement, a-priori, that certain combinations are not realistic, particularly as what is considered implausible has been found to be respondent specific (Yang et al 2019). Marten et al (2017) found that EQ-5D-5L level combinations assumed to be implausible (for example no problems with self-care combined with unable to do usual activities) actually appear in general population self-report data.…”
Section: Methodsmentioning
confidence: 99%
“…The design was specified to facilitate the estimation of the quality-of-life state dimension and survival duration level main effects, in addition to the interactions between the quality-of-life state dimensions and survival duration required to anchor the DCE TTO estimates on to the full health–dead scale [ 26 , 27 ]. Quality-of-life state combinations of dimension levels that were considered highly implausible in practice were identified in advance by the research team in consultation with our Project Advisory Group and constraints were applied in the design to avoid these implausible combinations occurring [ 34 , 35 ]. Implausible combinations included emotional well-being level 1 (“I am generally happy all of the time”) with pain management level 5 (“When I experience pain, it is well managed none of the time”) and emotional well-being level 1 (“I am generally happy all of the time”) with social relationships level 5 (i.e., “I have good social relationships with family and friends none of the time”).…”
Section: Methodsmentioning
confidence: 99%